Li2SiO3-coated Si / C / Si silicon-based negative electrode material and preparation method and application thereof
By covering the Li2SiO3 shell on the Si/C/Si hollow core layer and combining the mesoporous structure, the problem of volume changes in the silicon-based anode material during charging and discharging is solved, the conductive performance and lithium ion transmission rate are improved, and the capacity performance and cycling stability are significantly improved.
Patent Information
- Application Number
- CN202510066906.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
The silicon-based negative electrode material has serious volume changes during the charging and discharging process, resulting in low conductivity, degradation of capacity performance and cycle stability. The existing carbon coating methods have problems with low lithium ion transmission efficiency.
Li2SiO3@Si/C/Si silicon-based anode material was designed and synthesized. By covering the Li2SiO3 shell on the Si/C/Si hollow core layer, combining the Si/C/Si mesoporous structure, volume expansion is suppressed and lithium ion transmission rate is increased.
It effectively suppresses the volume expansion of silicon-based negative electrode material, improves the conductivity and lithium ion transmission rate, and significantly improves capacity, rate performance and cycling performance.
Smart Images

Figure CN119833619A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery negative electrode materials, and specifically relates to a Li2SiO3@Si / C / Si silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, silicon (Si) anode materials have become a candidate for replacing graphite anode materials to develop high energy density lithium-ion batteries, and are also a hot topic of current research, due to their advantages such as much higher theoretical gram capacity than graphite anode materials, lower lithium deintercalation potential (0.4V), and abundant resources (the theoretical gram capacity at room temperature is 3580mAh / g, and the theoretical gram capacity at high temperature is 4200mAh / g, which is about ten times the theoretical capacity of 372mAh / g of graphite anode materials). However, the conductivity of silicon anode materials themselves is low, and there is a serious volume change during the charge and discharge process (the volume expansion rate can reach more than 300%), which leads to the loss of electrical contact between particles or between particles and current collectors, and even the rupture and pulverization of electrode materials and the fall of active materials from current collectors, resulting in the problem of capacity performance attenuation and cycle stability performance degradation. Currently, carbon coating is often used to improve the volume expansion problem of silicon-based negative electrode materials. However, this method has the problem of low lithium ion transmission efficiency, and has limited effect on improving the capacity performance, rate performance, and cycle performance of the negative electrode materials, which limits its application in high energy density lithium-ion batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a Li2SiO3@Si / C / Si silicon-based negative electrode material and a preparation method and application thereof to address the problems of poor capacity performance, rate performance and cycle performance of existing silicon-based negative electrode materials.
[0004] In a first aspect, the present invention provides a Li2SiO3@Si / C / Si silicon-based negative electrode material.
[0005] Specifically, the Li2SiO3@Si / C / Si silicon-based negative electrode material includes a Si / C / Si hollow core layer and a Li2SiO3 shell layer coated on the outer surface of the Si / C / Si hollow core layer; the Si / C / Si hollow core layer includes a carbon layer and a Si element distributed on the inner surface and / or outer surface of the carbon layer; the Si / C / Si hollow core layer has a mesoporous structure.
[0006] In a preferred embodiment, the mass ratio of Si to C in the Si / C / Si hollow core layer is (1.4-2.0):1.
[0007] In a preferred embodiment, the thickness of the carbon layer is 0.5-1.5 nm.
[0008] In a preferred embodiment, the mesopore volume of the Si / C / Si hollow core layer is 5 to 6 cm 3 / g.
[0009] In a preferred embodiment, the D50 particle size of the Si / C / Si hollow core layer is 100-305 nm.
[0010] In a preferred embodiment, the thickness of the Li2SiO3 shell in the Li2SiO3@Si / C / Si silicon-based negative electrode material is 3 to 5 nm.
[0011] In a preferred embodiment, the D50 particle size of the Li2SiO3@Si / C / Si silicon-based negative electrode material is 100-350 nm.
[0012] In a second aspect, the present invention provides a method for preparing a Li2SiO3@Si / C / Si silicon-based negative electrode material. The preparation method comprises the following steps:
[0013] S1. The SiO2 particles are first coated with a carbon source, and then the resulting C@SiO2 precursor is first calcined to obtain C@SiO2 particles having a carbon layer coated on the surface of the SiO2 particles;
[0014] S2. The C@SiO2 particles are subjected to aluminothermic reduction reaction with aluminum powder, aluminum salt, and sodium salt, and the resulting product is acid-washed and dried to obtain Si / C / Si hollow sphere particles;
[0015] S3. The Si / C / Si hollow sphere particles are subjected to a second coating treatment in the presence of a silicon source and a lithium source and then subjected to a third calcination treatment to coat the outer surface of the Si / C / Si hollow sphere particles with Li2SiO3, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode materials.
[0016] In a preferred embodiment, in step S1, the mass ratio of the SiO2 particles to the carbon source is 1:(1-3).
[0017] In a preferred embodiment, the D50 particle size of the SiO2 particles is 100 to 300 nm.
[0018] In a preferred embodiment, the carbon source is selected from at least one of dopamine, glucose, sucrose, phenolic resin and citric acid.
[0019] In a preferred embodiment, the first coating treatment of the SiO2 particles and the carbon source is carried out in the presence of a tris buffer.
[0020] In a preferred embodiment, the conditions of the first coating treatment include: a temperature of 20 to 40° C. and a time of 4 to 8 hours.
[0021] In a preferred embodiment, the conditions of the first calcination treatment include: a temperature of 700 to 900° C. and a time of 1 to 3 hours.
[0022] In a preferred embodiment, in step S2, the mass ratio of the C@SiO2 particles to the aluminum powder, aluminum salt and sodium salt is 1:(0.6-1):(1-5):(0.6-1).
[0023] In a preferred embodiment, the conditions of the aluminothermic reduction reaction include: a temperature of 380 to 450° C. and a time of 10 to 14 hours.
[0024] In a preferred embodiment, in step S3, the second coating process comprises the following steps:
[0025] S31. The Si / C / Si hollow sphere particles are mixed with a silicate compound and water and subjected to a sol-gel reaction. The resulting product is subjected to a second calcination treatment to obtain a SiO2@Si / C / Si hollow sphere intermediate having a hollow Si / C / Si particle surface coated with SiO2;
[0026] S32. The SiO2@Si / C / Si hollow sphere intermediate is mixed with a lithium source and subjected to a third calcination treatment to obtain a Li2SiO3@Si / C / Si silicon-based negative electrode material.
[0027] In a preferred embodiment, the mass ratio of the Si / C / Si hollow sphere particles to the silicate compound is 1:(6-10).
[0028] In a preferred embodiment, the silicate compound is at least one selected from tetraethyl orthosilicate, tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate.
[0029] In a preferred embodiment, the temperature of the sol-gel reaction is 20-40°C.
[0030] In a preferred embodiment, the conditions of the second calcination treatment include: a temperature of 900-1100° C. and a time of 2-4 hours.
[0031] In a preferred embodiment, the sol-gel reaction of the Si / C / Si hollow sphere particles, silicate compounds and water is carried out in an organic solvent and / or under alkaline conditions.
[0032] In a preferred embodiment, the organic solvent is selected from at least one of ethanol, propanol and butanol.
[0033] In a preferred embodiment, the pH of the alkaline condition is 8-9.
[0034] In a preferred embodiment, the mass ratio of the SiO2@Si / C / Si hollow sphere intermediate to the lithium source is (4-6):1.
[0035] In a preferred embodiment, the lithium source is LiBH4.
[0036] In a preferred embodiment, the conditions of the third calcination treatment include: being carried out under high pressure conditions, at a temperature of 650 to 850° C., and for a time of 8 to 12 hours.
[0037] In a preferred embodiment, the third calcination treatment further includes a fourth calcination treatment.
[0038] In a preferred embodiment, the fourth calcination treatment is carried out under air atmosphere at a temperature of 400 to 600° C. for a time of 0.5 to 1 h.
[0039] In a third aspect, the present invention also provides a Li2SiO3@Si / C / Si silicon-based negative electrode material prepared by the above method.
[0040] In a fourth aspect, the present invention also provides the use of the above-mentioned Li2SiO3@Si / C / Si silicon-based negative electrode material in lithium-ion batteries.
[0041] The key of the present invention is to design and synthesize a Li2SiO3@Si / C / Si silicon-based negative electrode material with a specific structure, effectively inhibit the volume expansion of the silicon-based negative electrode material during the charge and discharge process, improve the conductivity and lithium ion transmission rate of the silicon-based negative electrode material, thereby improving the capacity performance, rate performance and cycle performance of the silicon-based negative electrode material. The reason for this may be that: on the one hand, the hollow and mesoporous structure of Si / C / Si cooperates with the Li2SiO3 shell structure to jointly inhibit the volume expansion of the silicon-based negative electrode material during the charge and discharge process, and the mesoporous structure is conducive to the transmission of lithium ions, and the carbon layer in Si / C / Si is conducive to improving the conductivity, thereby improving the capacity performance and rate performance of the silicon-based negative electrode material. On the other hand, the Li2SiO3 shell structure can not only play the role of pre-lithiation Si / C / Si hollow core layer, supplement the lithium ions consumed by the formation of SEI film, but also reduce the contact between the active Si element of the silicon-based negative electrode material and the electrolyte, form a stable SEI film, and improve the cycle stability of the silicon-based negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the XRD pattern of the Li2SiO3@Si / C / Si silicon-based negative electrode material prepared in Example 1;
[0043] Figure 2This is a TEM image of the Li2SiO3@Si / C / Si silicon-based negative electrode material prepared in Example 1;
[0044] Figure 3 is the EDS graph of C and Si of the Si / C / Si hollow sphere particles prepared in Example 1;
[0045] Figure 4 This is a graph showing the ammonia adsorption-desorption curve of the Si / C / Si hollow sphere particles prepared in Example 1. DETAILED DESCRIPTION
[0046] The Li2SiO3@Si / C / Si silicon-based negative electrode material provided by the present invention comprises a Si / C / Si hollow core layer and a Li2SiO3 shell layer coated on the outer surface of the Si / C / Si hollow core layer; the Si / C / Si hollow core layer comprises a carbon layer and a Si element distributed on the inner surface and / or outer surface of the carbon layer; the Si / C / Si hollow core layer has a mesoporous structure.
[0047] In the present invention, the mass ratio of Si to C in the Si / C / Si hollow core layer is preferably (1.4-2.0):1, such as 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1 or any value therebetween. At this time, a stable Si / C / Si hollow core layer structure can be better formed, giving the silicon-based negative electrode material a better ability to inhibit volume expansion, further improving the electrochemical performance of the silicon-based negative electrode material, and being conducive to better performance of its capacity performance during the charge and discharge process.
[0048] In the present invention, the thickness of the carbon layer is preferably 0.5-1.5 nm, such as 0.5 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.5 nm or any value therebetween. In this case, the carbon layer can further improve the conductivity of the silicon-based negative electrode material and facilitate the transition and transmission of lithium ions to improve its capacity performance and rate performance.
[0049] In the present invention, the D50 particle size of the Si / C / Si hollow core layer is preferably 100-305 nm, such as 100 nm, 150 nm, 200 nm, 250 nm, 280 nm, 305 nm or any value therebetween. The D50 particle size of the Li2SiO3@Si / C / Si silicon-based negative electrode material is preferably 100-350 nm, such as 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or any value therebetween. This is more conducive to shortening the transmission path of lithium ions, reducing the volume expansion of particles, and further improving the capacity performance, rate performance, and cycle performance of silicon-based negative electrode materials.
[0050] The term "D50 particle size" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%.
[0051] In the present invention, the mesopore volume of the Si / C / Si hollow core layer is preferably 5 to 6 cm 3 / g, such as 5cm 3 / g, 5.2cm 3 / g, 5.5cm 3 / g, 5.8cm 3 / g, 6cm 3 / g or any value therebetween. At this time, controlling the volume of the mesopores within the above preferred range is more conducive to reserving buffer space for the volume expansion of the silicon-based negative electrode material and providing more transmission channels for lithium ions, thereby giving it more ideal capacity performance, rate performance, and cycle performance.
[0052] In the present invention, the thickness of the Li2SiO3 shell layer in the Li2SiO3@Si / C / Si silicon-based negative electrode material is preferably 3 to 5 nm, such as 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm or any value therebetween. Under the premise of achieving complete coating of the Si / C / Si hollow core layer by Li2SiO3, not only can the volume expansion of the silicon-based negative electrode material be suppressed, but the lithium ions consumed in forming the SEI film can also be supplemented, thereby obtaining a silicon-based negative electrode material with better performance, and improving the capacity, the first charge and discharge efficiency and the cycle stability.
[0053] The preparation method of the Li2SiO3@Si / C / Si silicon-based negative electrode material provided by the present invention comprises the following steps:
[0054] S1. The SiO2 particles are first coated with a carbon source, and then the resulting C@SiO2 precursor is first calcined to obtain C@SiO2 particles having a carbon layer coated on the surface of the SiO2 particles;
[0055] S2. The C@SiO2 particles are subjected to aluminothermic reduction reaction with aluminum powder, aluminum salt, and sodium salt, and the resulting product is acid-washed and dried to obtain Si / C / Si hollow sphere particles;
[0056] S3. The Si / C / Si hollow sphere particles are subjected to a second coating treatment in the presence of a silicon source and a lithium source and then subjected to a third calcination treatment to coat the outer surface of the Si / C / Si hollow sphere particles with Li2SiO3, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode materials.
[0057] In the present invention, in step S1, the mass ratio of the SiO2 particles to the carbon source is preferably 1:(1-3), such as 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:3 or any value therebetween. At this time, it is more conducive to the carbon source to completely and evenly coat the SiO2 particles, which is convenient for the subsequent formation of Si / C / Si hollow sphere particles.
[0058] In the present invention, the D50 particle size of the SiO2 particles is preferably 100-300 nm, such as 100 nm, 150 nm, 200 nm, 250 nm, 280 nm, 300 nm or any value therebetween. This is more conducive to shortening the transmission path of lithium ions, reducing the volume expansion of particles, and further improving the capacity performance, rate performance, and cycle performance of silicon-based negative electrode materials.
[0059] In the present invention, specific examples of the carbon source include, but are not limited to: at least one of dopamine, glucose, sucrose, phenolic resin, and citric acid.
[0060] In the present invention, the conditions of the first coating treatment preferably include: a temperature of 20 to 40°C, such as 20°C, 25°C, 30°C, 35°C, 40°C or any value therebetween; and a time of 4 to 8h, such as 4h, 5h, 6h, 7h, 8h or any value therebetween.
[0061] In the present invention, the first coating treatment of the SiO2 particles and the carbon source is preferably carried out in the presence of tris buffer, which is more conducive to stabilizing the pH of the reaction system, promoting the hydrolysis of the carbon source, and coating more uniformly. Specifically, the first coating treatment of the SiO2 particles and the carbon source can be as follows: the SiO2 particles and the tris buffer are mixed and stirred at 20 to 40°C (such as 20°C, 25°C, 30°C, 35°C, 40°C or any value therebetween) for 0.5 to 1h (such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or any value therebetween), and then the carbon source is added and continued to be treated at 20 to 40°C for 4 to 8h, and the C@SiO2 precursor is obtained after separation, washing and drying.
[0062] In the present invention, the conditions of the first calcination treatment preferably include: a temperature of 700-900°C, such as 700°C, 750°C, 800°C, 850°C, 900°C or any value therebetween; and a time of 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween.
[0063] In the present invention, the aluminothermic reduction reaction generates a large number of ions and solvated electrons through the molten aluminum salt and sodium salt, and the single substance Al of the aluminum powder is oxidized to Al 3+ , thereby etching SiO2 to form SiO x, SiO x As the molten salt continues to be reduced, Si monomer eventually grows on the inner surface and / or outer surface of the carbon layer through the diffusion mechanism of the etching-reduction nucleation-growth process, thereby forming a Si / C / Si hollow shell structure.
[0064] In the present invention, the purpose of the pickling is to remove the byproducts of the aluminothermic reduction reaction and the residual raw material components. The acid used in the pickling is preferably at least one of hydrochloric acid, sulfuric acid and nitric acid. After the pickling, washing with water or a low-aliphatic alcohol organic solvent such as methanol or ethanol may also be included.
[0065] In the present invention, the mass ratio of the C@SiO2 particles to the aluminum powder, aluminum salt, and sodium salt is preferably 1:(0.6-1):(1-5):(0.6-1). Taking the mass of the C@SiO2 particles as 1 part by weight, the mass of the aluminum powder is preferably 0.6-1 part by weight, such as 0.6, 0.7, 0.8, 0.9, 1 part by weight or any value therebetween; the mass of the aluminum salt is preferably 1-5 parts by weight, such as 1, 2, 3, 4, 5 parts by weight or any value therebetween; the mass of the sodium salt is preferably 0.6-1 part by weight, such as 0.6, 0.7, 0.8, 0.9, 1 part by weight or any value therebetween. The aluminum salt is preferably selected from aluminum chloride and / or aluminum nitrate. The sodium salt is preferably selected from sodium chloride and / or sodium nitrate.
[0066] In the present invention, the conditions of the aluminothermic reduction reaction preferably include: a temperature of 380 to 450°C, such as 380°C, 390°C, 400°C, 410°C, 420°C, 450°C or any value therebetween; a time of 10 to 14 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or any value therebetween. At this time, the aluminothermic reduction reaction is more conducive to obtaining Si / C / Si hollow sphere particles with a hollow core layer structure and stability.
[0067] In the present invention, the second coating treatment may be to use various existing methods to combine the silicon source and the lithium source to the outer surface of the Si / C / Si hollow sphere particles, thereby obtaining the precursor material of Li2SiO3@Si / C / Si. The second coating treatment preferably includes the following steps:
[0068] S31. The Si / C / Si hollow sphere particles are mixed with a silicate compound and water and subjected to a sol-gel reaction. The resulting product is subjected to a second calcination treatment to obtain a SiO2@Si / C / Si hollow sphere intermediate having a hollow Si / C / Si particle surface coated with SiO2;
[0069] S32. The SiO2@Si / C / Si hollow sphere intermediate is mixed with a lithium source and subjected to a third calcination treatment to obtain a Li2SiO3@Si / C / Si silicon-based negative electrode material.
[0070] In the present invention, the mass ratio of the Si / C / Si hollow sphere particles to the silicate compound is preferably 1:(6-10), such as 1:6, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:10 or any value therebetween. At this time, the silicate compound can be evenly and completely coated on the outer surface of the Si / C / Si hollow sphere particles, which is beneficial to the subsequent formation of the Li2SiO3 shell layer.
[0071] In the present invention, specific examples of the silicate compounds include, but are not limited to, at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate.
[0072] In the present invention, the temperature of the sol-gel reaction is preferably 20-40°C, such as 20°C, 25°C, 30°C, 35°C, 40°C or any value therebetween.
[0073] In the present invention, the conditions of the second calcination treatment may include: the temperature is preferably 900-1100°C, such as 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value therebetween; the time is preferably 2-4h, such as 2h, 2.5h, 3h, 3.5h, 4h or any value therebetween.
[0074] In the present invention, the sol-gel reaction of the Si / C / Si hollow sphere particles, the silicate compound and water is preferably carried out in an organic solvent and / or under alkaline conditions. At this time, the presence of the organic solvent is conducive to the full mixing between the silicate compound and water, thereby facilitating the sol-gel reaction. The alkaline conditions can catalyze and promote the sol-gel reaction.
[0075] In a specific embodiment, the organic solvent is preferably at least one of ethanol, propanol and butanol. The pH of the alkaline condition is preferably 8 to 9, such as 8, 8.2, 8.5, 8.8, 9 or any value therebetween, which is more conducive to controlling the speed of the sol-gel reaction.
[0076] In a specific embodiment, the order and method of mixing the Si / C / Si hollow sphere particles with silicate compounds, water, and organic solvents are not specifically limited, and they can be added and mixed together at the same time, or some components can be mixed first and then the remaining components can be added and mixed. The method for the sol-gel reaction of the Si / C / Si hollow sphere particles with silicate compounds, water, and organic solvents under alkaline conditions can be as follows: after mixing the silicate compounds, water, and organic solvents, ultrasonic treatment is continued for 20 to 40 minutes, Si / C / Si hollow sphere particles are added, and the obtained mixture is evaporated to dry the solvent under alkaline conditions, and the obtained product is the SiO2@Si / C / Si hollow sphere precursor.
[0077] In the present invention, the mass ratio of the SiO2@Si / C / Si hollow sphere intermediate to the lithium source is preferably (4-6):1, such as 4:1, 4.5:1, 5:1, 5.5:1, 6:1 or any value therebetween.
[0078] In the present invention, the conditions of the third calcination treatment preferably include: conducting under high pressure conditions, such as mixing the SiO2@Si / C / Si hollow sphere intermediate with a lithium source and then conducting a third calcination treatment in an autoclave, the temperature is 650-850°C, such as 650°C, 700°C, 750°C, 800°C, 850°C or any value therebetween; the time is 8-12h, such as 8h, 9h, 10h, 11h, 12h or any value therebetween;
[0079] In the present invention, the third calcination treatment preferably includes a fourth calcination treatment for the purpose of removing impurities. The conditions of the fourth calcination treatment may include: being carried out in an air atmosphere, the temperature is preferably 400-600°C, such as 400°C, 450°C, 500°C, 550°C, 600°C or any value therebetween; the time is preferably 0.5-1h, such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or any value therebetween.
[0080] In addition, the terms "first", "second", "third" and "fourth" are only for the purpose of convenience of description and do not represent any special limitation on the type and quantity of technical features.
[0081] The present invention will be described in detail below through specific embodiments.
[0082] Example 1 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0083] S1. Mix 50g of monodisperse SiO2 nanospheres (D50=100nm) with 100mL of tris buffer, place in a 35℃ water bath and stir for 60min, add 100g of dopamine, and then continue to stir in a 35℃ water bath for 5h. Separate the precipitate by high-speed centrifugation, wash with deionized water and anhydrous ethanol several times, and dry at 60℃ for 6h to obtain C@SiO2 precursor, which is then transferred to a sintering furnace and sintered at 800℃ for 2h under a nitrogen protective atmosphere to obtain C@SiO2 particles with a carbon layer coated on the surface of the SiO2 particles.
[0084] S2. C@SiO2 particles were mixed with aluminum powder, aluminum chloride (AlCl3), and sodium chloride (NaCl) in a mass ratio of 1:0.85:3:0.87 and placed in a stainless steel container. Aluminothermic reduction reaction was carried out at 400°C in a nitrogen atmosphere for 12 hours. After cooling to room temperature, the reactants were washed with hydrochloric acid to remove by-products and residual salts, and then centrifuged and washed with anhydrous ethanol for multiple times. After vacuum drying at 60°C, Si / C / Si hollow sphere particles were obtained, with a D50 particle size of 100 nm and a mesopore volume of 6 cm 3 / g.
[0085] S3. 113 mL of deionized water, 45 mL of anhydrous ethanol, and 9.6 mL of tetraethyl orthosilicate (TEOS) were mixed and ultrasonically treated for 30 min, and then 1.2 g of Si / C / Si hollow sphere particles were added and ultrasonically treated for another 30 min. Then, the pH of the system was adjusted to about 8 with ammonia (NH3·H2O). The mixture was placed in a 35°C water bath and stirred at a constant temperature until the water was evaporated. The evaporated sample was vacuum dried at 80°C for 12 h to obtain a SiO2@Si / C / Si hollow sphere precursor. The SiO2@Si / C / Si hollow sphere precursor was placed in a sintering furnace, argon was introduced at high temperature, and the mixture was kept at 1000°C for 3 h. Then, the mixture was naturally cooled to room temperature to obtain a SiO2@Si / C / Si hollow sphere intermediate with SiO2 coated on the surface of the hollow Si / C / Si particles.
[0086] 200 mg SiO2@Si / C / Si hollow sphere intermediate was mixed with 40 mg LiBH4 in a glove box, then added into an autoclave and reacted at 750°C for 10 h with a heating rate of 4°C / min. After cooling to room temperature, it was taken out and heated to 500°C again in an air environment for 0.5 h. After cooling to room temperature, it was washed with anhydrous ethanol and deionized water, and vacuum dried at 60°C to obtain Li2SiO3@Si / C / Si silicon-based negative electrode material with a D50 particle size of 105 nm and a Li2SiO3 shell thickness of 4 nm.
[0087] Depend on Figure 1From the XRD graph, it can be seen that the silicon-based negative electrode material prepared in this embodiment has characteristic peaks of Li2SiO3 and Si, indicating that the Li2SiO3@Si / C / Si silicon-based negative electrode material was successfully prepared. Figure 2 The TEM image shows that the Li2SiO3@Si / C / Si silicon-based negative electrode material has a hollow structure. The EDS images of C and Si are shown in Figure 3 As shown in Figure 2, C and Si are evenly distributed on the hollow shell, indicating the successful preparation of Si / C / Si hollow sphere particles. Figure 4 The ammonia adsorption-desorption curve shows that the Si / C / Si hollow sphere particles have a mesoporous structure.
[0088] Example 2 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0089] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S1, SiO2 nanospheres with D50=200nm were used instead of SiO2 nanospheres with D50=100nm, and the other conditions were the same as those of Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 206nm, and the thickness of the Li2SiO3 shell was 4nm (the D50 particle size of the Si / C / Si hollow sphere particles was 200nm, and the mesopore volume was 5.2cm 3 / g).
[0090] Example 3 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0091] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S1, SiO2 nanospheres with D50=300nm were used instead of SiO2 nanospheres with D50=100nm, and the other conditions were the same as those in Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 305nm, the content of Li2SiO3 shell layer was 4nm thick (the D50 particle size of Si / C / Si hollow sphere particles was 300nm, and the mesopore volume was 5.8cm 3 / g).
[0092] Example 4 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0093] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of dopamine in step S1 was 75 g, and the amount of LiBH4 in step S3 was 50 mg, and the other conditions were the same as those in Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 107 nm, and the thickness of the Li2SiO3 shell was 5 nm (the D50 particle size of the Si / C / Si hollow sphere particles was 100 nm, and the mesopore volume was 6 cm 3 / g).
[0094] Example 5 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0095] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of dopamine in step S1 was 125 g, and the amount of LiBH4 in step S3 was 34 mg, and the other conditions were the same as those in Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 103 nm, and the thickness of the Li2SiO3 shell was 3 nm (the D50 particle size of the Si / C / Si hollow sphere particles was 100 nm, and the mesopore volume was 5.5 cm 3 / g).
[0096] Example 6 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0097] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S1, SiO2 nanospheres with D50=50nm were used instead of SiO2 nanospheres with D50=100nm, and the other conditions were the same as those of Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 55nm, and the thickness of the Li2SiO3 shell was 4nm (the D50 particle size of the Si / C / Si hollow sphere particles was 50nm, and the mesopore volume was 8.1cm 3 / g).
[0098] Example 7 Preparation of Li2SiO3@Si / C / Si silicon-based negative electrode material
[0099] Li2SiO3@Si / C / Si silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S1, SiO2 nanospheres with D50=500nm were used instead of SiO2 nanospheres with D50=100nm, and the other conditions were the same as those of Example 1, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode material, whose D50 particle size was 506nm, and the thickness of the Li2SiO3 shell was 4nm (the D50 particle size of the Si / C / Si hollow sphere particles was 500nm, and the mesopore volume was 4.2cm 3 / g).
[0100] Comparative Example 1
[0101] A reference silicon-based negative electrode material was prepared according to the method of Example 1, except that step S3 was not performed, and the remaining conditions were the same as those of Example 1, to obtain a hollow Si / C / Si silicon-based negative electrode material.
[0102] Comparative Example 2
[0103] 113 mL of deionized water, 45 mL of anhydrous ethanol, and 9.6 g of tetraethyl orthosilicate (TEOS) were mixed and ultrasonically treated for 30 min, and then 1.2 g of Si powder (D50 = 100 nm) was added and ultrasonically treated for another 30 min, and then the pH of the system was adjusted to about 8 with ammonia (NH3·H2O), and then the mixture was placed in a 35°C water bath and stirred at a constant temperature until the water was evaporated, and then the evaporated sample was vacuum dried at 80°C for 12 h to obtain a SiO2@Si precursor, and the SiO2@Si precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the mixture was kept at 1000°C for 3 h, and then naturally cooled to room temperature to obtain a SiO2@Si intermediate with Si particles coated with SiO2 on the surface;
[0104] 200 mg SiO2@Si intermediate was mixed with 40 mg LiBH4 in a glove box, then added into an autoclave and reacted at 750°C for 10 h with a heating rate of 4°C / min. After cooling to room temperature, it was taken out and heated to 500°C again in an air environment for 0.5 h. After cooling to room temperature, it was washed with anhydrous ethanol and deionized water, and vacuum dried at 60°C to obtain Li2SiO3@Si silicon-based negative electrode material with a D50 particle size of 105 nm and a Li2SiO3 shell thickness of 4 nm.
[0105] Comparative Example 3
[0106] A reference silicon-based negative electrode material was prepared according to the method of Example 1, except that step S2 was not performed, 50 g of Si powder (D50=100 nm) was used instead of 50 g of monodisperse SiO2 nanospheres (D50=100 nm) in step S1, and 1.2 g of C@Si particles prepared in step S1 of this example were used instead of 1.2 g of Si / C / Si hollow sphere particles in step S3. The remaining conditions were the same as in Example 1, and Li2SiO3@C@Si silicon-based negative electrode material was obtained.
[0107] Test Case
[0108] The silicon-based negative electrode material, carbon black and binder (sodium alginate) obtained in the above embodiments and comparative examples were mixed in a mass ratio of 3:1:1 to prepare a negative electrode sheet. The negative electrode sheet was assembled into a battery with a separator, a positive electrode sheet (lithium sheet) and an electrolyte (1M LiPF6 as a solute, dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) and its electrochemical performance was tested according to the following method. The results are shown in Table 1.
[0109] (1) First efficiency performance: The assembled battery was charged at a constant current of 0.1C to a cut-off voltage of 1.5V, and then discharged at a constant current of 0.1C to a cut-off voltage of 0.005V. The discharge capacity was divided by the charge capacity to obtain the first charge and discharge efficiency, referred to as the first efficiency.
[0110] (2) Rate performance: The assembled battery was subjected to first cycle charge and discharge capacity tests under constant current charging conditions of 0.1C and 1C, respectively, and the discharge capacity at 0.1C and 1C was recorded.
[0111] (3) Cycle performance: The assembled battery was tested on a battery test system (Blue Electric Test System) and charged and discharged 100 times at a constant current of 0.1C in the voltage range of 0.005 to 1.5V under room temperature conditions. The retention rate after 100 cycles was obtained by dividing the 100th discharge capacity by the 1st discharge capacity.
[0112] Table 1
[0113]
[0114]
[0115] It can be seen from the results in Table 1 that compared with comparative examples 1 to 3, the Li2SiO3@Si / C / Si silicon-based negative electrode materials provided by Examples 1 to 7 of the present invention have better initial efficiency performance and cycle performance, higher discharge capacity at 0.1C and 1C, and better rate performance.
[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A Li2SiO3@Si / C / Si silicon-based negative electrode material, characterized in that: The Li2SiO3@Si / C / Si silicon-based negative electrode material includes a Si / C / Si hollow core layer and a Li2SiO3 shell layer coated on the outer surface of the Si / C / Si hollow core layer; the Si / C / Si hollow core layer includes a carbon layer and a Si element distributed on the inner surface and / or outer surface of the carbon layer; the Si / C / Si hollow core layer has a mesoporous structure.
2. The Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 1, characterized in that: The mass ratio of Si to C in the Si / C / Si hollow core layer is (1.4-2.0):1; Preferably, the thickness of the carbon layer is 0.5 to 1.5 nm; Preferably, the mesopore volume of the Si / C / Si hollow core layer is 5 to 6 cm 3 / g; Preferably, the D50 particle size of the Si / C / Si hollow core layer is 100-305 nm.
3. The Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 1, characterized in that: The thickness of the Li2SiO3 shell in the Li2SiO3@Si / C / Si silicon-based negative electrode material is 3 to 5 nm; Preferably, the D50 particle size of the Li2SiO3@Si / C / Si silicon-based negative electrode material is 100 to 350 nm.
4. A method for preparing a Li2SiO3@Si / C / Si silicon-based negative electrode material, characterized in that: The preparation method comprises the following steps: S1. The SiO2 particles are first coated with a carbon source, and then the resulting C@SiO2 precursor is first calcined to obtain C@SiO2 particles having a carbon layer coated on the surface of the SiO2 particles; S2. The C@SiO2 particles are subjected to aluminothermic reduction reaction with aluminum powder, aluminum salt, and sodium salt, and the resulting product is acid-washed and dried to obtain Si / C / Si hollow sphere particles; S3. The Si / C / Si hollow sphere particles are subjected to a second coating treatment in the presence of a silicon source and a lithium source and then subjected to a third calcination treatment to coat the outer surface of the Si / C / Si hollow sphere particles with Li2SiO3, thereby obtaining Li2SiO3@Si / C / Si silicon-based negative electrode materials.
5. The method for preparing the Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 4, characterized in that: In step S1, the mass ratio of the SiO2 particles to the carbon source is 1:(1-3); Preferably, the D50 particle size of the SiO2 particles is 100 to 300 nm; Preferably, the carbon source is selected from at least one of dopamine, glucose, sucrose, phenolic resin and citric acid; Preferably, the first coating treatment of the SiO2 particles and the carbon source is carried out in the presence of a tris buffer; Preferably, the conditions of the first coating treatment include: temperature of 20-40°C and time of 4-8h; Preferably, the conditions of the first calcination treatment include: a temperature of 700 to 900° C. and a time of 1 to 3 hours; Preferably, in step S2, the mass ratio of the C@SiO2 particles to the aluminum powder, aluminum salt, and sodium salt is 1:(0.6-1):(1-5):(0.6-1); Preferably, the conditions of the aluminothermic reduction reaction include: a temperature of 380 to 450° C. and a time of 10 to 14 hours.
6. The method for preparing the Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 4, characterized in that: In step S3, the second coating process includes the following steps: S31. The Si / C / Si hollow sphere particles are mixed with a silicate compound and water and subjected to a sol-gel reaction. The resulting product is subjected to a second calcination treatment to obtain a SiO2@Si / C / Si hollow sphere intermediate having a hollow Si / C / Si particle surface coated with SiO2; S32. The SiO2@Si / C / Si hollow sphere intermediate is mixed with a lithium source and subjected to a third calcination treatment to obtain a Li2SiO3@Si / C / Si silicon-based negative electrode material; Preferably, the mass ratio of the Si / C / Si hollow sphere particles to the silicate compound is 1:(6-10); Preferably, the silicate compound is selected from at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate; Preferably, the temperature of the sol-gel reaction is 20 to 40°C; Preferably, the conditions of the second calcination treatment include: a temperature of 900 to 1100° C. and a time of 2 to 4 hours.
7. The method for preparing the Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 6, characterized in that: The sol-gel reaction of the Si / C / Si hollow sphere particles, silicate compounds and water is carried out in an organic solvent and / or alkaline conditions; Preferably, the organic solvent is selected from at least one of ethanol, propanol and butanol; Preferably, the pH of the alkaline condition is 8-9.
8. The method for preparing the Li2SiO3@Si / C / Si silicon-based negative electrode material according to claim 6, characterized in that: The mass ratio of the SiO2@Si / C / Si hollow sphere intermediate to the lithium source is (4-6):1; Preferably, the lithium source is LiBH4; Preferably, the conditions of the third calcination treatment include: being carried out under high pressure conditions, at a temperature of 650 to 850° C., and for a time of 8 to 12 hours; Preferably, the third calcination treatment further includes a fourth calcination treatment; Preferably, the fourth calcination treatment is carried out under air atmosphere at a temperature of 400 to 600° C. for a time of 0.5 to 1 h.
9. Li2SiO3@Si / C / Si silicon-based negative electrode material prepared by the method described in any one of claims 4 to 8.
10. Use of the Li2SiO3@Si / C / Si silicon-based negative electrode material according to any one of claims 1 to 3 and 9 in lithium-ion batteries.